Glycometabolic Control Does Not Affect Sexual Function in a Cohort of Women with Type 1 Diabetes: Results of an Observational Pilot Study - Cristian Petolicchio; Giordano Spacco; Eliana Delle Chiaie; Maria Grazia Calevo; Nicola Minuto; Davide Carlo Maggi; Diego Ferone; Marta Bassi; Francesco Cocchiara (Endocrines, 2025)
Background/Objectives: The association between sexual dysfunction and diabetes is well known, but few studies have investigated its prevalence in type 1 diabetes (T1D). The aim of this study was to evaluate the prevalence of sexual dysfunction in a group of women with T1D, regardless of their age, and to compare its different prevalences in women treated with different insulin regimens. Methods: The population included 77 women affected by T1D, of which 16 were on Multiple Daily Injections (MDI) and 61 on Continuous Subcutaneous Insulin Infusion (45 on Advanced Hybrid Closed Loop System with catheter and 16 on patch pump). All participants completed the Female Sexual Function Index (FSFI), a questionnaire that evaluates several aspects of sexual function. Another questionnaire that evaluated general features, diabetes-specific features and sexual-specific features was proposed to every participant. Results: The overall prevalence of female sexual dysfunction was 49.3%. A correlation was demonstrated between the prevalence of female sexual dysfunction and age; another correlation was found between the prevalence of female sexual dysfunction and dyadic status. No correlation between glycemic control and sexual dysfunction was found. Conclusions: Women with T1D presented a high prevalence of sexual dysfunction, independently from glycometabolic disease control and insulin regimens; on the other hand, a significant correlation was demonstrated with age and dyadic status. Evaluation of sexual function in women with T1D appears to be important in clinical settings independently from disease control.